Gaya Pengasuhan Orang Tua Terhadap Kepribadian Anak - Fauziah Nasution; Tryana Fauziyah; Annisa Wibowo; Siti Khairuna Salwa Lubis; Sintia Agustina (Bersatu: Jurnal Pendidikan Bhinneka Tunggal Ika, 2024)
In general, parenting is an interaction relationship between parents, namely father and mother. And their children, which involves aspects of the parents' attitudes, values and beliefs as a form of nurturing effort, showing their authority over the child and one of the parents' responsibilities in delivering their child. Towards maturity. This research aims to provide readers with an understanding of parental parenting styles regarding children's personalities. The data collection technique used in this research, where the data comes from books. Scientific journals, literature that is suitable as a source for the research that the author will research. The results of the research show that parental patterns consist of theree types, on of which is authoritarian parenting where parents demand that children follow the rules without asking the child's opinion. This makes children tend to lack self-confidence and form an unhealthy inner child